Activation of the developmental pathway neurogenin‐3/microRNA‐7a regulates cholangiocyte proliferation in response to injury. Issue 4 (25th August 2014) - Marzioni, Marco; Agostinelli, Laura; Candelaresi, Cinzia; Saccomanno, Stefania; De Minicis, Samuele; Maroni, Luca; Mingarelli, Eleonora; Rychlicki, Chiara; Trozzi, Luciano; Banales, Jesus M.; Benedetti, Antonio; Baroni, Gianluca Svegliati
<x xml:space="preserve">Abstract</x> The activation of the biliary stem‐cell signaling pathway hairy and enhancer of split 1/pancreatic duodenal homeobox‐1 (Hes‐1/PDX‐1) in mature cholangiocytes determines cell proliferation. Neurogenin‐3 (Ngn‐3) is required for pancreas development and ductal cell neogenesis. PDX‐1‐dependent activation of Ngn‐3 initiates the differentiation program by inducing microRNA (miR)−7 expression. Here we investigated the role Ngn‐3 on cholangiocyte proliferation. Expression levels of Ngn‐3 and miR‐7 isoforms were tested in cholangiocytes from normal and cholestatic human livers. Ngn‐3 was knocked‐down in vitro in normal rat cholangiocytes by short interfering RNA (siRNA). In vivo, wild‐type and Ngn‐3‐heterozygous (+/−) mice were subjected to 3, 5‐diethoxycarbonyl‐1, 4‐dihydrocollidine (DDC) feeding (a model of sclerosing cholangitis) or bile duct ligation (BDL). In the liver, Ngn‐3 is expressed specifically in cholangiocytes of primary sclerosing cholangitis (PSC) patients and in mice subjected to DDC or BDL, but not in normal human and mouse livers. Expression of miR‐7a‐1 and miR‐7a‐2 isoforms, but not miR‐7b, was increased in DDC cholangiocytes compared to normal ones. In normal rat cholangiocytes, siRNA against Ngn‐3 blocked the proliferation stimulated by exendin‐4. In addition, Ngn‐3 knockdown neutralized the overexpression of insulin growth factor‐1 (IGF1; promitotic effector) observed after exposure to exendin‐4, but not that of PDX‐1 or VEGF‐A/C. Oligonucleotides anti‐miR‐7 inhibited the exendin‐4‐induced proliferation in normal rat cholangiocytes, but did not affect Ngn‐3 synthesis. Biliary hyperplasia and collagen deposition induced by DDC or BDL were significantly reduced in Ngn‐3+/− mice compared to wild‐type. Conclusion: Ngn‐3‐dependent activation of miR‐7a is a determinant of cholangiocyte proliferation. These findings indicate that the reacquisition of a molecular profile typical of organ development is essential for the biological response to injury by mature cholangiocytes. (Hepatology 2014;60:1324–1335)